Thoracic actinomycosis: a rare occurrence - Waqas Jehangir; Bhumesh Vaidya; Souad Enakuaa; Nazar Raoof; John R. Middleton; Abdalla Yousif (MDPI AG, 2016)
Actinomyces israelii is a branching anaerobic bacilli microorganism that can be identified as normal flora throughout various portions of the human alimentary canal. It is crucial to establish a diagnosis as treatment will vary depending on the clinical form of the disease. We report a case of a 78-year-old man who initially presented with an acute onset of respiratory distress displayed contrast leakage on computed tomography from the site of a previously inserted esophageal stent for an unsuccessful surgical repair of an esophageal rupture. In addition to the contrast leakage, the presence of a bronchopulmonary fistula imaging prompted the need for further investigation. Our patient was empirically treated with antibiotics and obtained blood cultures, which returned positive A. israelii.